Association of meniscal lesion and cranial cruciate ligament insufficiency in dogs - Ferrigno, Cássio Ricardo Auada (2012)
The following study describes meniscus ruptures associated to cranial cruciate ruptures, in 34 dogs of different breeds, ages and weights. Before surgery the animals underwent clinical and radiographic examinations. All animals presented either total or partial cranial cruciate ruptures: 21 (24.14%) of the animals didn’t present any meniscus lesions, and the rest (75.86%) presented only a medial meniscus lesion. The lesions found in the medial meniscus were the following: 33 stifles (37.93%) presented with eversion of the caudal pole (Type 1), 15 (17.24%) showed a bucked handle lesion (Type 6), 3 (3.45%) presented with fibrillation lesion (Type 4), 3 (3.45%) multiple fibrillation lesion (Type 3), 3 (3.45%) longitudinal lesion (Type 2), 1 (1.15%) lesion type 7 and 10 (11.49%) presented multiple lesion. Surgical procedure for cranial cruciate rupture included: tibial tuberosity advancement (TTA) (49 stifle), tibial plateau leveling osteotomies (TPLO) (15 stifle), closing wedge osteotomy (CWO) (14 stifle), extracapsular (4 stifle) and meniscectomy alone (5 stifle), and all these techniques guaranteed weight baring and return to function in the first week after surgery, with no complications. Through this study we could demonstrate that meniscus tear is highly associated to cranial cruciate rupture and that the most common is type 1 (eversion of the caudal pole) and that cronicity of the lesion increases the probability of meniscus tear.